Kritische Normenforschung in den Internationalen Beziehungen Neue Wege und metatheoretische Perspektiven - Engelkamp, Stephan; Glaab, Katharina; Graf, Antonia (Internationale Beziehungen, 2021)
Constructivist norm research is a lively and growing research programme in the field of international relations. Unsurprisingly, its increasing differentiation over the last three decades has raised questions about the ability to communicate across different academic camps. This edited volume enables dialogue by identifying commonalities and differences among academic camps from a metatheoretical perspective. The authors theoretically and empirically highlight new paths for critical norm research, foregrounding reflexivity and contingency, and critically discussing key concepts such as contestation, intersubjectivity and normativity. In this way, they reveal new paths towards critical norm research in this field. With contributions by Stephan Engelkamp, Sassan Gholiagha, Katharina Glaab, Antonia Graf, Hannes Hansen-Magnusson, Eva Herschinger, Maren Hofius, Daniel Jacobi, Kai Koddenbrock, Friederike Kuntz, Bastian Loges, Holger Niemann, Judith Renner, Frank Sauer, Henrik Schillinger, Linda Wallbott and Lisbeth Zimmermann.